2020
DOI: 10.1155/2020/1206247
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Flavonoid Extract of Lotus Leaf on Alcohol-Induced Gastric Injury by Antioxidant Capacity in Mice

Abstract: The aim of this study was to investigate the antioxidant effects of flavonoid extract of lotus leaf (FELL) in vitro and in mice with gastric injury and elucidate the inhibitory effect of FELL on alcohol-induced gastric injury by antioxidant capacity. Gastric juice volume and acid value were measured in the established alcohol-induced acute gastric injury model in mice. Hematoxylin and eosin staining demonstrated the morphological changes in the gastric mucosa. FELL improved the alcohol-induced gastric lesions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Yang et al found that apple polyphenols improved the antioxidant capacity of grass carp, protected grass carp from inflammation, and reduced the expression of IL-6 ( Yang et al, 2021 ). Chen et al found that lotus leaf flavonoids extract significantly reduced the levels of IL-6, IL-12 and TNF-α with the increase in concentration ( Chen et al, 2020 ). Our results indicated that orange vinegar and its main components could reduce the expression of inflammatory factors induced by CML.…”
Section: Resultsmentioning
confidence: 99%
“…Yang et al found that apple polyphenols improved the antioxidant capacity of grass carp, protected grass carp from inflammation, and reduced the expression of IL-6 ( Yang et al, 2021 ). Chen et al found that lotus leaf flavonoids extract significantly reduced the levels of IL-6, IL-12 and TNF-α with the increase in concentration ( Chen et al, 2020 ). Our results indicated that orange vinegar and its main components could reduce the expression of inflammatory factors induced by CML.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that lotus leaf extract enhances the antioxidant capacity in alcohol-induced gastric injury mice [ 41 ] and high-fat diet-induced obese mice [ 42 ], including the ability to increase SOD, CAT, GSH, and GSH-PX and decrease the levels of MDA and NO. We further found that LLFE also significantly inhibits the levels of MDA and NO in D-Gal/LPS-induced mice and increases the levels of serum antioxidant enzymes and compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, recent research has focused on the search for efective plant-derived substances, which can be good sources for food additives as colorant, sweetener, preservative, and aroma [9][10][11][12][13][14][15][16]. Currently, there is a signifcant increase in the use of plant-derived colorants with a protective action against various perturbations and diseases such as diabetes, cancers, osteoporosis, and hyperlipidemia [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. It is notable that the ingestion of O. stricta prickly pears also improves platelet function and hemostatic balance, thus contributing to prevent atherosclerotic risks [33,34].…”
Section: Introductionmentioning
confidence: 99%